Growth and neurodevelopmental outcomes of children with in utero growth restriction due to placental insufficiency and modification by maternal HIV status - Hoffman, Marinel (University of Pretoria, 2024)
Thesis (PhD (Nutrition))--University of Pretoria, 2024.